2019
DOI: 10.1167/tvst.8.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Assessment of Corneal Erosions Using Optical Coherence Tomography and Automated Grading of Fluorescein Staining in a Rabbit Dry Eye Model

Abstract: Purpose To evaluate the potential use of anterior segment spectral domain optical coherence tomography (AS-SD-OCT) combined with an automated grading of fluorescein staining for assessment of corneal erosions in a rabbit short-term dry eye model. Methods Twenty-one New Zealand white rabbits were anesthetized and eyes were kept open for 140 minutes to induce acute corneal desiccation. Rectangular scans of the cornea were performed using Spectralis AS-SD-OCT. Total cornea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In a recent study, it has been reported that a significant correlation exists between the percentage of corneal fluorescein staining area and the percentage of the area of epithelial erosion detected by AS-OCT, in rabbits with experimental dry eye models. 28 Abou Shousha et al reported that ultra-high resolution OCT reveals irregularity of epithelial surface, which can be improved after treatment in patients with dry eye. 20 Another study by Deinema et al investigated the corneal reflectivity using AS-OCT in patients with DED and healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, it has been reported that a significant correlation exists between the percentage of corneal fluorescein staining area and the percentage of the area of epithelial erosion detected by AS-OCT, in rabbits with experimental dry eye models. 28 Abou Shousha et al reported that ultra-high resolution OCT reveals irregularity of epithelial surface, which can be improved after treatment in patients with dry eye. 20 Another study by Deinema et al investigated the corneal reflectivity using AS-OCT in patients with DED and healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescein staining was performed by instilling 20 μL 2% fluorescein solution on the ocular surface. 16 After removing excess fluorescein, the cornea and the superior bulbar conjunctiva were photographed with a digital camera under blue light. The extent of fluorescein staining of the cornea and superior conjunctiva was scored using a modified NEI scoring method.…”
Section: Methodsmentioning
confidence: 99%
“…The corneal damage can be severe, depending on the duration of the desiccative stress. The model has been used to screen drug effects or to study the contribution of desiccative stress to the pathophysiology of DED ( 63 , 94 ).…”
Section: Rabbit Models Of Dedmentioning
confidence: 99%